The search for WondLa - DiTerlizzi, Tony (DiTerlizzi, Tony. Wondla trilogy, 2012)
Living in isolation with a robot on what appears to be an alien world populated with bizarre life forms, a twelve-year-old human girl called Eva Nine sets out on a journey to find others like her. Features "augmented reality" pages, in which readers with a webcam can access additional information about Eva Nine's world